Inhibitory effect of a resin coat-containing prereacted glass fillers on the enamel demineralization of the primary teeth: An in vitro pilot study - R Rabiabasree; R Krishnakumar; Anand S Prabhu; N Sathyajith Naik; K K Shashibhushan; K Janarthanan (Wolters Kluwer Medknow Publications, 2019)
Background: With an increasing interest in preventive strategies, pedodontics research is now more focused on developing newer materials and techniques to coat the primary teeth to prevent onset of new carious lesions. Aim: The aim of this study is to evaluate the inhibitory effect of prereacted glass (PRG) filler-containing resin coat on enamel demineralization of the primary teeth. Subjects and Methods: Eight de-rooted primary caries-free teeth sectioned into 4 mm × 4 mm were divided into either experimental group which received the PRG barrier coat or control group which was left uncoated. These were then immersed in acid buffer at pH 4.5 for 3 days. Mineral content was evaluated by scanning electron microscopy with energy dispersive X-ray analysis. Statistical Analysis: Data were collected and analyzed statistically using paired Student's "t" test, with a P < 0.05 being considered statistically significant. Results: When the calcium/phosphorous (Ca/P) ratio (wt%) which is indicative of the mineral content of enamel was compared, the values were higher for the experimental group than that for the control group and the association was statistically significant (P < 0.01). Conclusion: The higher Ca/P ratio of experimental group was suggestive of the ability of PRG barrier coat to inhibit enamel demineralization in the primary teeth.